2022
DOI: 10.1029/2022gl100121
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Antarctic Bottom Water Entering the Brazil Basin in a Planetary Geostrophic Inverse Model

Abstract: To understand the deep ocean's role in climate change, it is critical to understand how heat and CO 2 , absorbed at the surface, make their way throughout the deep ocean over decades to centuries, transported by complex current systems and modified by deep ocean mixing. This understanding should be grounded in an observational description of existing deep ocean circulation, something that is currently unavailable, except in limited areas. Given the impracticality of directly measuring the weak, time-mean deep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In addition to the total mass constraints, eight regional constraints across several longitude and depth ranges were introduced to reduce this underdetermined system (Table 1). These constraints have been previously applied in earlier studies of the South Atlantic Ocean as in other inverse models (Table 1; Hogg et al., 1982; Warren & Speer, 1991; Zenk et al., 1999), although the recent study of Finucane and Hautala (2022) suggested that the bottom transport estimated in the Hunter Channel by Zenk et al. (1999) could be overestimated.…”
Section: Relative Geostrophic Transport and Inverse Modelmentioning
confidence: 86%
See 1 more Smart Citation
“…In addition to the total mass constraints, eight regional constraints across several longitude and depth ranges were introduced to reduce this underdetermined system (Table 1). These constraints have been previously applied in earlier studies of the South Atlantic Ocean as in other inverse models (Table 1; Hogg et al., 1982; Warren & Speer, 1991; Zenk et al., 1999), although the recent study of Finucane and Hautala (2022) suggested that the bottom transport estimated in the Hunter Channel by Zenk et al. (1999) could be overestimated.…”
Section: Relative Geostrophic Transport and Inverse Modelmentioning
confidence: 86%
“…In addition to the total mass constraints, eight regional constraints across several longitude and depth ranges were introduced to reduce this underdetermined system (Table 1). These constraints have been previously applied in earlier studies of the South Atlantic Ocean as in other inverse models (Table 1; Hogg et al, 1982;Warren & Speer, 1991;Zenk et al, 1999), although the recent study of Finucane and Hautala (2022) suggested that the bottom transport estimated in the Hunter Channel by Zenk et al (1999) could be overestimated. We have also included new constraints for 34.5°S from recent studies by Chidichimo et al (2021), Kersalé et al (2019), and Meinen et al (2017) using data from the moored arrays deployed along this section as part of the South Atlantic MOC Basin-wide Array (SAMBA) (Ansorge et al, 2014;Meinen et al, 2013Meinen et al, , 2017Meinen et al, , 2018.…”
Section: Massmentioning
confidence: 89%